The Role of Images in Freshwater Conservation in South Africa: An Analysis of Images and Perceptions of Freshwater Fish - Burnette, Jessica (Department of Biological Sciences, 2022)
Freshwater biodiversity is highly threatened, but under-represented in media, and less well known than marine and terrestrial counterparts. The current lack of public awareness of freshwater species and ecosystems may limit freshwater conservation as a popular cause. The manner in which species are portrayed in the popular media can influence awareness and support for conservation. In this digital age, images in particular may play a major role in public support for conservation. In this study, I examined images sourced from the web of ten native South African freshwater fish species and images of a general search for ‘freshwater fish South Africa' to investigate the kinds of images people are exposed to. Results show that only 28% of speciesspecific images showed the fish in a water habitat, with the remaining images showing the fish out of water, often with the presence of humans. I then conducted an online survey of people's perceptions of freshwater fish images. Respondents were shown images of native South African fish in water and out of water. From this survey, 73% of respondents stated they would choose images of fish in water in their natural habitat to communicate the importance of conserving freshwater ecosystems and freshwater fish. Over 95% of respondents, agreed that images play an important role in rallying support for nature conservation in general. When shown images of fish in water, 57% of respondents stated the in-water images evoked a desire to know more about freshwater environments and 49% stated a desire to know more about freshwater fish. The survey also investigated respondent willingness to donate money and time to freshwater conservation and explored whether showing either ‘in-water' or ‘out of water' images beforehand influenced this response. The results suggested that the type of images presented beforehand had little to no effect on willingness to donate, but other factors such as gender, natural sciences background, and history of visiting freshwater environments influenced respondent willingness to donate time and money. Overall this study suggests that future considerations should be given to how freshwater fish species are portrayed in science communication and environmental education through imagery.